2002
DOI: 10.1046/j.1365-2265.2002.01537.x
|View full text |Cite
|
Sign up to set email alerts
|

99mTechnetium pentavalent dimercaptosuccinic acid scintigraphy in the follow‐up of clinically nonfunctioning pituitary adenomas after radiotherapy

Abstract: Functional imaging of pituitary remnant adenomas (> 10 mm in size) by (99m)Tc(V)DMSA depicts viable pituitary adenoma remnants. This approach may be of clinical value in patients with clinically nonfunctioning adenomas to monitor the effects of radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The overall sensitivity of 99m Tc(V)-DMSA and 99m Tc-HYNIC-TOC, by the qualitative scintigraphic analysis described, was significantly lower, and is consistent with previous studies that concluded that scintigraphy with these tracers was not sufficiently sensitive for the evaluation of patients with secreting PAs 44,50.…”
Section: Discussionsupporting
confidence: 89%
“…The overall sensitivity of 99m Tc(V)-DMSA and 99m Tc-HYNIC-TOC, by the qualitative scintigraphic analysis described, was significantly lower, and is consistent with previous studies that concluded that scintigraphy with these tracers was not sufficiently sensitive for the evaluation of patients with secreting PAs 44,50.…”
Section: Discussionsupporting
confidence: 89%
“…Aggressive fi bromatosis [1] and squamous cell carcinoma of head and neck cancer [2,3] are also well-known soft tissue tumors that show Tc-99m (V) DMSA uptake. There are also a limited number of reports about positive uptake of Tc-99m (V) DMSA in breast cancer [11], hepatocellular carcinoma [12], and nonfunctioning pituitary adenomas after radiotherapy [13].…”
Section: Discussionmentioning
confidence: 99%
“…The initial definitive management of pituitary adenomas is almost always surgical, followed by postoperative radiotherapy to reduce the risk of tumor regrowth [74,75]. Colao found that, in addition to a reduction in residual tumor size after radiotherapy, a significant decrease in V DMSA uptake was observed in all patients with a favourable prognosis [76]. In this study, V DMSA appeared to be an easy and repeatable test to assess the viability of pituitary adenomas and to monitor the response to radiotherapy in this tumor type.…”
Section: Phosphate Transport: Technetium 99m-pentavalent Dimercaptosumentioning
confidence: 98%